TATA KELOLA KEBIJAKAN PENGURANGAN KETERGANTUNGAN IMPOR GANDUM DALAM PERSPEKTIF KETAHANAN PANGAN INDONESIA - Farid Bayu Murti; Benny Osta Nababan; Arief Safari; Aulia Rizki Wicaksono (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Indonesia’s dependence on wheat imports has continued to increase along with the expansion of wheat-based food consumption and the growth of processed food industries. This condition creates vulnerabilities in the national food security system, as wheat supply is highly affected by global market dynamics, geopolitical conflicts, international price fluctuations, and exchange rate volatility. This study aims to analyze the factors driving wheat import dependence, its implications for food security, and policy alternatives that can be implemented to reduce such dependence. The study employs a qualitative-analytical approach supported by secondary data from statistical documents, policy reports, academic literature, and limited expert judgment. Expert judgment was conducted involving four respondents from government, academia/research, and the food industry. The findings show that wheat import dependence is not only caused by agro-climatic limitations, but also by the structure of the national food industry, consumption patterns, and the limited integration of wheat risk management into food policy governance. The expert assessment indicates that local food diversification and partial wheat flour substitution received the highest average scores, each at 3.25. Strategic wheat reserves received an average score of 3.00, while the development of tropical-adaptive wheat varieties received the lowest score of 2.25. These findings suggest that reducing wheat import dependence requires a hybrid policy approach that combines local food diversification, partial wheat flour substitution, and strategic wheat reserves as a stabilization instrument. This study emphasizes the importance of cross-sectoral food governance involving government, industry, academia, and society.